Maize heads cereals league in Africa - Technical Centre for Agricultural and Rural Cooperation (Technical Centre for Agricultural and Rural Cooperation, 1992)
Maize was introduced into Africa between the 16th and 18th centuries, and is now the continent's premier cereal crop (40% of all cereals harvested in 1989). Kenya and southern Africa grow the most, though because of its sensitivity to drought...